Creative Dislocation: an Experiment in Collaborative Historical Research. (20th September 2020) - Bickers, Robert; Cole, Tim; Dudley, Marianna; Hanna, Erika; McLellan, Josie; Pooley, William; Williamson, Beth
Abstract: This article introduces an experiment in collaborative historical practice. It describes how six historians visited the East Devon village of Branscombe, with the aim of creatively engaging with the present and past of the village. This was a collaborative and collective act of what we term here 'creative dislocation'. By dislocating from our usual routines, subjects, places, methods, and styles, and adopting creative methods and constraints, we aimed to shed light on the role of creativity in the historical research process. Our experiment resulted in six pieces of writing – three of which are presented here. However, a key argument of this article is that creativity lies in process as much as in the finished product. Creative work happened at each stage of the research process, in ways that were not always immediately visible in the final written pieces. The creativity in historical research and writing does not necessarily lie in opposition to archival explorations and fact-driven narratives, but can also lie within them. Creativity informs the questions we ask, our ways of working with the archive and our approach to writing.